Pemberian Probiotik Lactobacillus Helveticus Rosell-52 Dan Lactobacillus Rhamnosus Rosell-11 Untuk Mengatasi Konstipasi Pada Usia Lanjut - Retno Wahyuningsih (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. In old age there will be many changes along with the aging process. One of these changes is changes in the gastrointestinal system. One problem that many suffer from old age in the gastrointestinal system is constipation or constipation. Some Lactobacillus species used in probiotic supplements, namely L. helveticus and L. rhamnosus, have a role in maintaining healthy digestive function. Research Methods. This study used a randomized pre-post test control group design. The subjects in this study were 46 people living in the PSTW Puspakarma Mataram, divided into two groups, namely the treatment group was given probiotics, and the control group was given a placebo. The status of constipation or not is obtained by using the questionnaire (questionnaire) of Agarwal Sharma's constipation with 8 question items. Research Result. The results of statistical tests show that there is an effect of probiotic consumption with the incidence of constipation (p <0.05). From the results of the study it was found that there was an effect of the consumption of probiotics with the occurrence of constipation. There was a difference in the incidence of constipation between the treatment groups given probiotics Lactobacillus helveticus Rosell-52 and Lactobacillus rhamnosus Rosell-11 with groups given only placebo. In the treatment group there was a reduction in the incidence of constipation and in the control there were still many cases of constipation in the elderly. Conclusion. There is an influence on the consumption of probiotics with the occurrence of constipation.